POTENSI PENGEMBANGAN PERKEBUNAN VANILI SEBAGAI AGROWISATA BERBASIS KEARIFAN LOKAL DI DESA GENGGELANG LOMBOK UTARA - Ria Astuti; I Putu Gede; Agusman Agusman; Syech Idrus; Lalu Masyhudi (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2022)
This study discusses the potential for developing vanilla plantations as agro-tourism based on local wisdom in the village of Genggelang, Lombok Utara. So that the purpose of this research is to describe the potential of vanilla agro-tourism in the village of Genggelang, Lombok Utara and to formulate the efforts that can be made towards the development of vanilla agro-tourism in the village of Genggelang, Lombok Utara. This study uses a qualitative approach with data collection techniques in the form of interviews, observations, documentation and questionnaires. The data analysis technique uses SWOT analysis to formulate a vanilla plantation development strategy as Agrotourism. The results of this study, namely, the potential of human resources, natural resources, tourist attractions, Accessibility, facilities and infrastructure, agro-tourism, and local wisdom were then analyzed using SWOT analysis. The results obtained show the SO (strength-opportunity) and WO (weakness-opportunity) strategies, namely by utilizing all the strength factors of the Vanilla Plantation to get the opportunities it has, as well as the ST (Strength-Threat) and WT (weaknesses-threat) strategies, namely Limiting the number of tourists visiting Vanilla plantation objects by providing entrance tickets and Maintaining the original behavior and culture of the community to increase local wisdom in tourist attractions. This can be done with strategic solutions to make a basic plan for agro-tourism areas, maintain and preserve vanilla plantation land traditionally, improve the management of vanilla plantations to become a souvenir product for tourists and the government conducts socialization related to the importance of agro-tourism.